Apolipoprotein "E”, health and risk for stroke in contemporary communities (Research, Society and Development, 2019)
This paper presents an analysis of noncommunicable chronic diseases (CDNTs) in the literature and aims to analyze the risk of Apolipoprotein E (ApoE) and stroke in the contemporary community. Its objective is to analyze the relationship between Apolipoprotein E and Stroke polymorphism based on the risk analysis between ApoE and Stroke genetic polymorphism. This is a descriptive, exploratory and qualitative study. It is concluded that several authors in their study report the increased risk of stroke with ApoE and its alleles.